2016
DOI: 10.1111/jocn.13244
|View full text |Cite
|
Sign up to set email alerts
|

Screening and brief intervention for unhealthy substance use in patients with chronic medical conditions: a systematic review

Abstract: Although small, the international evidence base suggests that screening with the Alcohol Use Disorders Identification Test or Alcohol Use Disorders Identification Test-C and brief interventions for primary care patients with chronic medical conditions, delivered by nurses or other providers, are effective for identifying unhealthy substance use and associated with healthy behaviours and improved outcomes. Lacking are studies screening for illicit drug use, and using single-item screening tools, which could be … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
23
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 33 publications
(25 citation statements)
references
References 42 publications
1
23
0
1
Order By: Relevance
“…Furthermore, patients and families need to learn approaches to reduce the risk of transmission and how to change behaviours that can accelerate disease such alcohol use. Brief alcohol interventions can be effectively administered by nurses (Timko, Kong, Vittorio, & Cucciare, ). In the USA, the healthcare system is uniquely challenging for low‐income, minority residents because of access, continuity and coverage issues that must be overcome to achieve a cure for this chronic infection.…”
Section: Resultsmentioning
confidence: 99%
“…Furthermore, patients and families need to learn approaches to reduce the risk of transmission and how to change behaviours that can accelerate disease such alcohol use. Brief alcohol interventions can be effectively administered by nurses (Timko, Kong, Vittorio, & Cucciare, ). In the USA, the healthcare system is uniquely challenging for low‐income, minority residents because of access, continuity and coverage issues that must be overcome to achieve a cure for this chronic infection.…”
Section: Resultsmentioning
confidence: 99%
“…La literatura científica nacional e internacional seña-la que la consejería breve, es decir una sola sesión de 30 minutos, puede motivar el cambio en etapas iniciales del consumo (Martínez et al, 2010;Tavera & Martínez, 2008;Timko, Kong, Vittorio, & Cucciare, 2016;Winters, Fahnhorst, Botzet, Lee, & Lalone, 2012). Sin embargo, valdría la pena profundizar en esta hipótesis y determinar qué tanto una sola sesión bien estructurada puede lograr una transformación en los jóvenes que se inician en el uso de sustancias.…”
Section: Conclusionesunclassified
“…However, studies have shown that management of hypertension, cardiovascular disease, and diabetes at primary care level is suboptimal [4–7], and only half of the patients achieve their target blood pressure and blood sugar level, which increases their risk for CVD events [4,5]. Some of the challenges in treating and managing chronic conditions are suboptimal adherence to management guidelines by the physicians [5,8], lack of regular patient monitoring and undiagnosed comorbidities such as anxiety, depression, and alcohol use disorders which can contribute to failure to follow treatment plans [911]. Mobile health (mHealth) technologies are being advocated to strengthen the health system, and systematic reviews have shown that an mHealth-based Clinical Decision Support System (CDSS) improves preventive care and the physician’s clinical decision quality in hypertension and diabetes management [8] although the evidence on their effects on cardiovascular outcomes is limited [12].…”
Section: Introductionmentioning
confidence: 99%